SISTEM INFORMASI KEHADIRAN SOPIR PADA PT BLUE BIRD TBK BERBASIS WEB - Putri Hayati; Kukuh Harsanto; Achmad Rizki Nur Fauzie; Anwar Rifai (Universitas Budi Luhur, 2025)
The transportation industry heavily depends on effective human resource management. PT Blue Bird Tbk, a leading transportation company in Indonesia, requires an information management system to efficiently oversee its human resources, particularly the operational team. This study aims to create a website driver attendance monitoring framework for implementation at PT Blue Bird Tbk. The goal is to enhance operational team management efficiency by providing a web-based application that assists in work scheduling and attendance tracking. Besides offering flexibility in data management, the system enables access to real-time information. Using the waterfall model for software development, the research encompasses the stages of requirements analysis, system design, implementation, testing, and maintenance. During the analysis phase, Data was gathered by means of firsthand observation and interviews to understand existing business processes. The application was developed with ReactJS and Go for the user interface and system logic, while MySQL was utilized for database management. The black box technique test findings demonstrate that all features in the web-based driver attendance monitoring information system function properly. This research resulted when creating and designing a web-based system that allows real-time and efficient monitoring of driver attendance. Thus, the management of PT Blue Bird Tbk can monitor driver attendance more effectively.